Signals, synapses, and synthesis: how new proteins control plasticity - Zukin, R. Suzanne; Richter, Joel; Bagni, Claudia (Frontiers in Neural Circuits, 2009)
Localization of mRNAs to dendrites and local protein synthesis afford spatial and temporal regulation of gene expression and endow synapses with the capacity to autonomously alter their structure and function. Emerging evidence indicates that RNA binding proteins, ribosomes, translation factors and mRNAs encoding proteins critical to synaptic structure and function localize to neuronal processes. RNAs are transported into dendrites in a translationally quiescent state where they are activated by synaptic stimuli. Two RNA binding proteins that regulate dendritic RNA delivery and translational repression are Cytoplasmic Polyadenylation Element Binding Protein (CPEB) and Fragile X Mental Retardation Protein (FMRP). The Fragile X syndrome is the most common known genetic cause of autism and is characterized by the loss of FMRP. Hallmark features of the Fragile X syndrome include dysregulation of spine morphogenesis and exaggerated metabotropic glutamate receptor-dependent long term depression, a cellular substrate of learning and memory. Current research focuses on mechanisms whereby mRNAs are transported in a translationally repressed state from soma to distal process and are activated at synaptic sites in response to synaptic signals.